PERUBAHAN SOSIAL KOMUNITAS PESISIR DAN IMPLIKASINYA TERHADAP DEGRADASI SUMBERDAYA ALAM DI KAWASAN DELTA MAHAKAM, KALIMANTAN TIMUR - Cahyadi, M.Si, Jimmy (Jurnal Harpodon Borneo, 2011)
This article studies about social change from in perpective of historical sosio of community who live in region Delta Mahakam Kalimantan Timur. Social change from coastal area community Delta Mahakam in the form of institution change influencing social system, has lessened local area carrying capacity is affecting high of resources degradation which is mangrove area is wide in world.  This article substance, that change of community social Delta Mahakam started by some complex social processes like resident increase, contradiction (conflict and integration) between group and community communications process Delta Mahakam with other community having different in perpective background about Delta Mahakam. Social Management Approach Based On Trust Communication between the parties is having importance is alternative submitted in this article end. Keywords : social change, degradation SDA, social management based on trust communication, sustainability